Review of advances in plant biotechnology (International rice research institute, 1989)
An international symposium on genetic manipulation in crops was held at CIMMYT in Mexico, from 29-31 Aug, 1988. Beginning with a keynote address that looked into the scientific, social, economic and ethical implications of genetic manipulation in crops, the symposium continued by presenting 27 papers. Four specific areas were covered: (1) anther culture and haploid breeding: (2) protoplast culture, somatic hybridization and transformation systems; (3) distant hybridization; and (4) somatic embryogenesis and somaclonal variation. Crops covered in these presentations include rice, wheat, citrus, stylo, and potato. Six poster presentations are also included dealing with rice, wheat, cassava and cotton (CAB Abstract)